Young adult perspectives on dignity in mental healthcare - Kieffer, Stephanie (Nursing ethics, 2025)
BackgroundThe promotion of human dignity lies at the core of ethical patient-centered healthcare and encompasses the inherent worth, value, and respect that patients deserve. Little is known about how this concept applies to the distinct needs and challenges faced by young adults (young adults) seeking mental healthcare.ObjectiveThis study hopes to provide deeper insights into young adults perspectives about the factors that contribute to and hinder their sense of human dignity within the mental healthcare system.Research designA descriptive qualitative approach was used to explore participant perspectives through semi-structured interviews. Thematic analysis was performed on the interview transcripts by three coders.Participants and research contextThirteen young adults patients attending an ambulatory mental health clinic for mood and anxiety disorders in London, Ontario participated in this study.Ethical considerationsThis study was conducted in accordance with the Declaration of Helsinki. It was approved by the Health Sciences Research Ethics Board at the University of Western Ontario.Findings/resultsYound adults interviewed emphasize equality and equity as crucial aspects of dignity, value agency and involvement in healthcare decision-making as well as opportunities to engage with peers, and recognize system wide constraints as a barrier to feeling as though they have dignity within the healthcare system.ConclusionsWhile the young adults interviewed acknowledged that dignity is inherent to all people, they emphasized that all people are not treated as though they have dignity either in mental healthcare or in broader society based on their social location. To provide dignity affirming mental healthcare for young adults, clinicians should: approach their relationship with clients from a lens of cultural humility to provide individualized care, directly involve clients in their treatment plans, encourage client connection with their peers and communities, and actively consider and address systemic challenges that impact client wellbeing and sense of dignity at the societal level.